Effect of oxygen/argon gas ratio on the structure and optical properties of sputter-deposited nanocrystalline HfO2 thin films. Issue 5 (June 2015) - Ramana, C.V.; Vargas, M.; Lopez, G.A.; Noor-A-Alam, M.; Hernandez, M.J.; Rubio, E.J.
Abstract: Nanocrystalline hafnium oxide (HfO2 ) thin films have been produced under variable reactive oxygen (O2 ) fractionation ( Г ) employing Hf metal for reactive sputter-deposition. The effect of Г on the HfO2 compound formation, structure, morphology and optical properties has been evaluated. Without oxygen, the films of hexagonal phase of Hf metal were grown. Films grown at different O2 pressure are nanocrystalline, monoclinic HfO2 with ( 1 ¯ 11 ) texturing. The optical properties of HfO2 films have been evaluated using spectroscopic ellipsometry (SE). The optical constants and their dispersion profiles indicate that the best optical-quality HfO2 films are formed at O2 ratio of ≥0.2. The index of refraction ( n ) profiles derived from SE measurements follow the Cauchy dispersion relation. The correlation between oxygen-fraction and optical properties in HfO2 films is established.